2016
DOI: 10.1016/s1473-3099(16)00124-9
|View full text |Cite
|
Sign up to set email alerts
|

The spread of hepatitis C virus genotype 1a in North America: a retrospective phylogenetic study

Abstract: Background The timing of the initial spread of hepatitis C genotype 1a in North America is controversial. In particular how and when HCV reached extraordinary prevalence in specific demographic groups remains unclear. We sought to quantify, using all available HCV sequence data and phylodynamic methods the timing of the spread of HCV genotype 1a in North America. Methods We screened 45,316 publicly available HCV genotype 1a sequences for location and genotype then conducted phylogenetic analyses of available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…For example, the subtype 1a analysis in Australia, where the distance between the predicted root and the oldest available sequence is the largest, the HPD intervals around tMRCA are also large. The robustness of coalescent analyses in predicting HCV epidemics has already been established [18], and a recent study using this method on subtype 1a data in North America yielded a very similar prediction to that reported here regarding the timing of the epidemic [31]. Regarding the epidemiological modeling, the data are dependent on reported numbers in national surveys and notification systems, which may be affected by underreporting.…”
Section: Discussionsupporting
confidence: 74%
“…For example, the subtype 1a analysis in Australia, where the distance between the predicted root and the oldest available sequence is the largest, the HPD intervals around tMRCA are also large. The robustness of coalescent analyses in predicting HCV epidemics has already been established [18], and a recent study using this method on subtype 1a data in North America yielded a very similar prediction to that reported here regarding the timing of the epidemic [31]. Regarding the epidemiological modeling, the data are dependent on reported numbers in national surveys and notification systems, which may be affected by underreporting.…”
Section: Discussionsupporting
confidence: 74%
“…transfusions. 27 Such exposure is now largely prevented through standard infection control practices. Some baby boomers may also have been infected through injection drug use or other risk behaviors.…”
Section: The Profiles Have Multiple Uses Including Tomentioning
confidence: 99%
“…These reactions to the disease have been cited as contributing to delay in HCV diagnosis of up to 28 years in the UK (Harris, Ward, & Gore, ) and may also prompt patients to avoid receiving care after diagnosis. Patients and their families also need to be educated about HCV so that the patient diagnosis is not always seen as being due to personal behaviours such as injection drug use because it is now understood to have diverse causes including incidental infection through routine health care decades ago (Joy et al., ). Furthermore, patients and families need to learn approaches to reduce the risk of transmission and how to change behaviours that can accelerate disease such alcohol use.…”
Section: Resultsmentioning
confidence: 99%
“…Most subjects admitted to worrying about how their lifestyle and substance use behaviours might have resulted in HCV infection. Although it is important to reinforce eliminating risky behaviours such as sharing dirty needles, new analyses of phylogenetic patterns of HCV infection in the USA suggested that nosocomial/iatrogenic factors likely played a major role in HCV transmission from the 1940s through 1960s when, for example, patients could have been inadvertently infected because of ineffective sterilisation practices (Joy et al., ). Destigmatising how patients acquired HCV can alleviate some of the strain of dealing with this diagnosis and may also reduce the sense of isolation because of being ashamed to share this diagnosis with others.…”
Section: Discussionmentioning
confidence: 99%